2023
DOI: 10.3389/fpsyg.2023.1111332
|View full text |Cite
|
Sign up to set email alerts
|

Starting university during the pandemic: First-year international students’ complex transitions under online and hybrid-learning conditions

Abstract: International education activities suddenly halted due to the COVID-19 pandemic, severely disrupting student mobility and academic learning. Many educational institutions have delivered programs to students through digital devices globally rather than in situ. Such a shift presents a unique opportunity to assess the impact of online and hybrid education for international students. This qualitative study interviewed 30 international students who had arrived on campus and shared their first-year university trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Our study was theoretically informed by Schlossberg et al's (1995) African American (e.g., Montgomery, 2017;Museus, 2014), and mainly used with IMDS in Englishspeaking countries (Belle at al., 2022;Montgomery, 2017;Wang, 2023). We believe our study demonstrates that these models may also be applied to studies on international student populations in non-English speaking contexts.…”
Section: Limitations and Future Researchmentioning
confidence: 72%
See 2 more Smart Citations
“…Our study was theoretically informed by Schlossberg et al's (1995) African American (e.g., Montgomery, 2017;Museus, 2014), and mainly used with IMDS in Englishspeaking countries (Belle at al., 2022;Montgomery, 2017;Wang, 2023). We believe our study demonstrates that these models may also be applied to studies on international student populations in non-English speaking contexts.…”
Section: Limitations and Future Researchmentioning
confidence: 72%
“…These models complement each other and together provide a comprehensive exploration of resources and types of support from individual and institutional perspectives. These models have been previously used in research on international students (e.g., Ballo et al, 2019;Belle et al, 2022;Montgomery, 2017;Wang, 2023), and are particular to the characteristics of an international student population, such as the IMDS in this study.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…A qualitative study conducted in China indicated hopelessness, uncertainty, worry, lack of interest and focus, lack of support, financial difficulties, social pressure, sleep disorders, and increased smoking among international students [28]. Therefore, visa and financial issues, language skills, acculturation problems, poor social support systems, cultural and social adjustment, academic adaptation, homesickness, and lack of knowledge about the healthcare system are some examples of the challenges faced by international students in particular [17,[43][44][45][46].…”
Section: Plos Onementioning
confidence: 99%